Family abuse targeting queer family members: An argument to address problems of visibility in local services and civic life - Donovan, Catherine (Journal of family violence, 2024)
PurposeTo draw attention to the invisibility of family abuse victimisation of lesbian, gay, bisexual and/or trans folk and its impacts; and the lack of appropriate, confident, skilled, formal responses to family abuse victimisation. In addition to argue that local strategic commitment is required to address structural discrimination faced by queer folk and to positively invite those victimised to seek help from local services.MethodA multi-method local study in a Central Bedfordshire, a County in England was conducted with an online survey, interviews and focus groups with local LGBT+ communities and practitioners.ResultsThe data suggests worryingly high reporting of family abuse particularly for trans participants. At the same time our data, in line with others, shows help-seeking to be low other than to informal sources of help especially friends. In addition professionals appear underconfident about how to respond appropriately.ConclusionsFamily abuse targeting queer folk is a significant problem and under-recognised. This is in part due to the mainstream domestic abuse sector associating family abuse with racially minoritised and/or faith communities and particular forms of violence such as “honour” abuse, forced marriage and female genital mutilation. Family abuse victimising queer folk is relatively invisible despite profound social, mental and physical health impacts. Practitioners in this study describe a lack of confidence, skills and knowledge about their practice responses to queer folk which needs to be addressed through training. However, we also conclude that the wider civic context can also play a part in sending messages to local queer folk that local services are for them and that there is a role for civic leaders to improve the visibility and confidence of local queer folk as citizens.